Mechanizmy perswazji pośredniej w tekstach media relations - Sujkowska-Sobisz, Katarzyna (Stylistyka, 2021)
This article treats abo ut functions of media relations texts. lt is proved that in spite of their authors’ declarations; in such texts dominates persuasive function. Mechanisms ofindirect persuasion were described thanks to using methods offered by cognitive linguistic and given by R. Langacker, G. Lako ff and M. Johnson. The authors of MR texts deliberately use the following existing in language_ methapors: THE INSTITUTION I S A WINNER, THE INSTITUTION IS A FRIEND, THE INSTITUTION IS A MAN, THE INSTITUTION’S ACTIVITY IS SPORTS COMPETITION, THE INSTITUTION’S ACTIVITY IS WAR.